Pentaho data integration cookbook : over 100 recipes for building open source ETL solutions with Pentaho data integration - Meadows, Alex; Pulvirenti, Adrián Sergio; Roldá, María Carina (Packt Publishing, 2013)
Pentaho Data Integration Cookbook Second Edition is written in a cookbook format, presenting examples in the style of recipes. This allows you to go directly to your topic of interest, or follow topics throughout a chapter to gain a thorough in-depth knowledge. Pentaho Data Integration Cookbook Second Edition is designed for developers who are familiar with the basics of Kettle but who wish to move up to the next level. It is also aimed at advanced users that want to learn how to use the new features of PDI as well as and best practices for working with Kettle.